Perancangan dan Pembangunan Sistem Informasi E-Surat RT/RW untuk Pelayanan Administrasi Surat Berbasis Web pada Kelurahan Padang Besi - Muhammad Ikhsan (GLOBAL SCIENTS PUBLISHER, 2026)
Mail administration services in Padang Besi Village still rely on manual processes that require residents to come in person, submit physical documents, wait for verification, and then pick up their letters, resulting in long queues and poorly structured archives. This study designed and built a web-based RT/RW e-Mail Information System in Padang Besi Village to digitize the flow of letter submission, verification, and issuance. The system provides user registration, online letter submission, uploading required documents, verification by officers, letter data management, and automatic letter generation in PDF format using templates. Implementation and testing results indicate that the system makes it easier for residents to submit letters and assists RT/RW officers in managing, monitoring the process, and storing archives in a structured manner. Thus, it is hoped that mail administration services in Padang Besi Village will be faster, more effective, transparent, and digitally documented.